Enhancement on protonation (H+) with incorporation of flexible ethylene carbonate in CMC–PVA–30 wt % NH4NO3 film - M. A., Saadiah; Y., Nagao; A. S., Samsudin (Elsevier Ltd, 2021)
In the present work, carboxymethyl cellulose (CMC)–polyvinyl alcohol (PVA)–NH4NO3 with the addition of ethylene carbonate (EC) based polymer blend electrolyte (PBE) was explored. The complexes of PBE with addition of EC revealed that an interaction of the –OH and –COO− of the CMC–PVA blend with the dissociation of H+ from NH4NO3 provides a flexibility pathway for ion hopping. The optimum ionic conductivity at room temperature was found to be 3.92 × 10−3 S/cm for the sample containing 6 wt.% EC with an increment of amorphous phase and thermal stability. Based on the Impedance-Nyquist theoretical approach, it was shown that the ionic conductivity with cation transference number (= 0.48) of the PBE is primarily influenced by the ionic mobility as well as the ions diffusion coefficient. The findings verified that the CMC–PVA–NH4NO3–EC possesses favorable conduction properties upon physical structural modification as a promising polymer electrolyte.